Is heart-type fatty acid binding protein (H-FABP) a valid marker of arterial stiffness in patients with systemic sclerosis? Arterial stiffness in systemic sclerosis - Öztürk, Ercüment; Yılmaz, Sema; Tuncez , Abdullah; Aygül , Nazif; Ünlü , Ali; Vatansev , Hüsamettin (Journal of Surgery and Medicine, 2022)
Background/Aim: Both micro- and macro-vascular involvement has been researched in systemic sclerosis (SSc) for many years. In this study, the relationship of arterial stiffness with heart-type fatty acid binding protein (h-FABP), which is well-accepted as a cardiac marker, was investigated for the first time. Methods: In this case-control study, 40 patients diagnosed with SSc between the ages of 18 and 65 were included. Thirty healthy individuals of similar age and gender were included as the control group. Patients were excluded from the study if they had cardiovascular risk factors, active infections, and/or malignancies. Along with detecting biochemical markers in the blood, results from methods, such as 24-h blood pressure Holter recordings, pulse-wave velocities (PWV), and echocardiograms (ECHO) were obtained from patients. Results: The homocysteine mean level was higher in the patient group than in the control group (P < 0.001). H-FABP and asymmetric dimethylarginine (ADMA) means were similar between the two groups (P = 0.286 and P = 0.340, respectively). Vascular parameters, including mean arterial pressure (MAP), augmentation index normalized to the 75 /min heart rate (AIx @ 75), and PWV were also similar between the two groups (P = 0.498, P = 0.382 and P = 0.180, respectively). Conclusion: It can be concluded that no ongoing myocardial damage occurs based on normotensive Holter findings, normal h-FABP levels, and ECHO findings in our patients. It is suggested that vasodilatory treatments, such as pentoxifylline and calcium channel blockers, which the patients receive for SSc treatment due to Raynaud Syndrome, may protect them from hypertension and therefore offer protection from myocardial damage.